Analisis Kontribusi Pajak Daerah Dan Retribusi Terhadap Pendapatan Asli Daerah (PAD) Kota Sorong Tahun 2018-2021 - Way, Fretelin R; Djaelani, Yustiana (Jurnal Ekonomi Bisnis Digital, 2024)
This study aims to find out how the contribution of advertisement tax, entertainment tax, hotel tax and land and building tax (PBB) to Local Own Revenue. The object of this research is Badan Pengelolaan Pajak dan Retribusi Daerah (BP2RD). The data used in this study are secondary data and primary data. The technique used in this research is document review by collecting documents related to this research, namely target data and realization of regional tax revenues and levies as well as regional income data. And the data obtained in this study by conducting interviews and direct observation at Badan Pengelolaan Pajak dan Retribusi Daerah (BP2RD). The results of this study indicate that based on the calculation of local tax contributions (advertisement tax, entertainment tax, hotel tax and land and building tax on regional income (PAD) from 2018-2021 in Sorong City, there are several criteria, namely very less, less and moderate. And it can be concluded that for levies that have the highest contribution value, namely in 2021, which is worth 5% and the lowest is in 2018 with a value of 1%.